2015
DOI: 10.3329/bpj.v17i2.22339
|View full text |Cite
|
Sign up to set email alerts
|

Practice of Hospital Pharmacy in Bangladesh: Current Perspective

Abstract: Although hospital pharmacists are recognized for its importance as health care provider in many developed countries, in most developing countries it is still underutilized. The aim of the present study was to summarize the current scenario of pharmacy practices in four hospitals of Bangladesh and to identify the pharmacist's rolesin these seftap. The study was conducted through convenient sampling method using a well-designed 14-item questionnaire to collect the opinions from the respondents. The results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Hospital pharmacy practice has just begun in some modern private hospitals in Bangladesh, which are inaccessible to most people because of the high cost of these hospitals to patients [49]. People are totally unknown to the responsibilities of hospital pharmacist, even they don't seek for recruit for hospital pharmacist in any hospital except a few aristocrat hospitals [50]. A Dhaka survey found nearly 50% of the respondents with acute respiratory disease (ARI) symptoms identified local pharmacies as their first point of care.…”
Section: Underutilization Of Hospital Pharmacymentioning
confidence: 99%
“…Hospital pharmacy practice has just begun in some modern private hospitals in Bangladesh, which are inaccessible to most people because of the high cost of these hospitals to patients [49]. People are totally unknown to the responsibilities of hospital pharmacist, even they don't seek for recruit for hospital pharmacist in any hospital except a few aristocrat hospitals [50]. A Dhaka survey found nearly 50% of the respondents with acute respiratory disease (ARI) symptoms identified local pharmacies as their first point of care.…”
Section: Underutilization Of Hospital Pharmacymentioning
confidence: 99%
“…Although hospital pharmacists are recognized for its importance as health care provider in many developed countries, in most developing countries it is still underutilized or underestimated [45][46][47][48]. Hospital pharmacy practice is just started in some private modern hospitals in Bangladesh which is inaccessible for the majority of peoples due to high patients cost of these hospitals [49]. People are totally unknown to the responsibilities of hospital pharmacist, even they don't seek for recruit for hospital pharmacist in any hospital except a few aristocrat hospitals [50].…”
Section: Under Utilization Of Hospital Pharmacymentioning
confidence: 99%
“…Challenges resulting from an increment in the number of medicines available and lack of adherence have changed the conversation of pharmacists toward a caring attitude. As a result of this situation, the pharmacy practice has come to be viewed as an incredibly significant vocation in the interdisciplinary team that provides medical services (Paul et al, 2014). In emerging regions, the pharmacy occupation is indeed falling behind in comparison to industrialized nations in the sense that pharmacy practitioners have never been acknowledged as a section of the medical team, neither by the population nor by healthcare practitioners (Said et al, 2020) Recently, investigators in the United Kingdom revealed that the majority of pharmacists were committed to producing advice to physicians as well as patient (Paul et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of this situation, the pharmacy practice has come to be viewed as an incredibly significant vocation in the interdisciplinary team that provides medical services (Paul et al, 2014). In emerging regions, the pharmacy occupation is indeed falling behind in comparison to industrialized nations in the sense that pharmacy practitioners have never been acknowledged as a section of the medical team, neither by the population nor by healthcare practitioners (Said et al, 2020) Recently, investigators in the United Kingdom revealed that the majority of pharmacists were committed to producing advice to physicians as well as patient (Paul et al, 2014). Clinical pharmacy services need to be available to all patients as part of normal care, according to the Society of Hospital Pharmacists of Australia (SHPA), because clinical pharmacists play significant role in minimizing the frequency of adverse medication events (Roy et al, 2015) According to the research conducted by Rezwan- Ul-Haque et al (2018), pharmaceutical caregivers have a considerable positive influence on healthbased on measurement and health care expenses over the long run.…”
Section: Introductionmentioning
confidence: 99%